Innovation environments for the creative industry - Silva, Marcela Guimarães (2018)
This study seeks to identify the participation of the creative industry and the creative class in the environments dedicated to innovation. To do so, it is based on literature review on the Maker's Movement, innovation environments, and the creative industry, and on a quantitative research, in which the data of the 2017 Coworking Brazil Census and the Fab Lab Brazil Network are analyzed. The results show that innovation environments grow from the birth of new forms of work and relationships in the work environment and as a result of technological advances, which can not be interpreted as a trend, but as a way of strengthening the sectors and the creative class.